Evaluación de la calidad de la carrera de Administración Pública-ESPAM-MFL, acorde a la evaluación externa de universidades y escuelas politécnicas, OCT/2021-AGOST/2022 - Arauz Barreiro, Gema Guadalupe (2022)
This research work was carried out with the objective of evaluating the quality of the ESPAM MFL Public Administration career according to the Evaluation model of Universities and Polytechnic Schools during the academic period Oct/2021-August/2022. The study reviews theoretical aspects that make up its support. Likewise, in the methodological development, the work was located in the spaces where the Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López" operates, specifically in the area of Public Administration. The type of research was exploratory and descriptive, applying field and propositional research, with a mixed approach that helped to use quantitative and qualitative methodologies for the development of the research, relying on inductive, deductive and analytical methods. The sample was intentional and was made up of students from the 5th, 6th, 7th, 8th and 9th levels of the Public Administration career. The survey and the interview were applied in data collection. The study allows us to conclude that the levels of compliance according to the scale of the standards of the substantive functions, according to the Evaluation model applicable in the Public Administration career, are mostly at a level of Approach to compliance, however They have detected limitations that require an overcoming plan to achieve the improvement of the academic quality in the Public Administration career in the institution and to be able to achieve improvements in the processes and in the axes involved.